Didymella pinodella: An Important Pea Root Rot Pathogen in France to Watch Out For? - Adnan Šišić; Jelena Baćanović-Šišić; Fernanda M. Gamba; Maria R. Finckh (Journal of Fungi, 2024)
Root rot pathogens restrict pea and wheat production globally. In the EU, pea and pea-based cereal mixtures are being promoted; however, root rot pathogen dynamics in such mixtures are poorly understood. Winter pea and wheat were grown either in pure stands or in mixtures in the field in western France, and the severity of root rot in pea, wheat, and their mixtures, as well as the key pathogens associated with these crops, were assessed. Disease severity was moderate in pea and low in wheat, with no effect of sowing pattern. Didymella pinodella, a previously unreported pathogen in the pea–root rot complex in France, emerged as the most dominant pathogen in pea. It also occurred in low frequencies in wheat. Subsequent greenhouse aggressiveness tests showed that ten of the commonly grown pea cultivars in France lack resistance to D. pinodella. Among the Fusarium spp. isolated, F. avenaceum was the most frequent, occurring at similar frequencies in pea and wheat. In conclusion, D. pinodella may be an important pea root rot pathogen in France and there is a lack of resistance in the tested pea cultivars. In addition, F. avenaceum is a shared pathogen of wheat and pea.